COMPARATIVE ANALYSIS OF IDIOMS IN BRITISH AND UZBEK CULTURES: A CASE STUDY OF "JANE EYRE" - Komil Olimovich Yaratov (Modern American Journals, 2025)
This article explores a comparative analysis of idioms within English and Uzbek cultures, based on Charlotte Brontë’s renowned novel ‘Jane Eyre’, a classic of English literature. Idioms, as linguistic units that reflect national mindset, customs, and values, serve to illuminate both the similarities and differences between these two cultural spheres. The English idioms found in ‘Jane Eyre’ are translated into Uzbek, and examined in terms of semantic aspects, cultural features, and contextual compatibility. Furthermore, by comparing them to equivalent Uzbek idioms, the article investigates strategies of cultural adaptation and linguistic translation. The findings underscore the importance of accounting for cultural context in the fields of linguistics and translation studies.
Keywords: Idioms, cultural differences, Jane Eyre, English literature, Uzbek language, translation theory, linguistic analysis, intercultural communication, language and culture, equivalence.